Emergence patterns for client design requirements. (July 2015) - Haug, Anders
Abstract : This paper focuses on a central topic in design communication studies, namely the elicitation of clients' design requirements. Based on interviews with ten industrial designers, the paper develops a conceptual framework that includes definitions of emergence patterns for client design requirements, potential communicative problems associated with these emergence patterns, and overall guidelines for addressing specific emergence patterns. The proposed conceptual framework aims at enabling designers to elicit clients' design requirements more efficiently and providing a foundation for future design communication research. Highlights: A classification of design requirement emergence patterns. Identification of the potential problems related to different emergence patterns. Overall guidelines for addressing different emergence patterns. Empirical studies supporting the contributions.